Female Sex, Fibromyalgia Diagnosis, Obesity, Tobacco Use, Preoperative Opioid Use, and Postoperative Recurrent Instability Are Risk Factors for Return to the Emergency Department 1 Year After Arthroscopic Shoulder Stabilization - Jacqueline M. Brady, M.D.; Isaac Lapite, M.D.; Albert Yim, B.S.; Jung U. Yoo, M.D. (Arthroscopy, Sports Medicine, and Rehabilitation)
Purpose: To identify risk factors for return to the emergency department (ED) 1 year after arthroscopic shoulder stabilization and to evaluate secondary outcomes related to postoperative opioid use and recurrent shoulder instability. Methods: We retrospectively identified patients aged 18 to 30 years old undergoing first-time arthroscopic shoulder stabilization (Current Procedural Terminology code 29806). The PearlDiver database was queried for patients between 2017 and 2019 with minimum of 3 months preoperatively to 24 months postoperative assessment, to analyze returns to the emergency department (ED), 1-year postsurgery opioid use, and recurrent instability. Results: Among 12,223 patients, 2,643 (21.6%) patients had at least 1 ED visit within 1-year postoperation. Factors significantly associated (P < .01) included sex (odds ratio [OR] 0.65), obesity (OR 1.71), tobacco use (OR 3.57), perioperative interscalene nerve block (OR 1.23), and recurrent instability (OR 1.49). When the analysis was carried out in the 642 (5.3%) patients with 3 or more postoperative ED visits, significant predictors (P < .01) were female sex (OR 0.49), fibromyalgia (OR 1.42), obesity (OR 1.96), tobacco use (OR 4.25), preoperative opioid use (OR 1.53), nerve block (OR, 1.36), and recurrent instability (OR 2.19). At 1 year postoperative, 2,160 (17.7%) patients were still taking opioids, with significant predictors (P < .01) of age (OR 1.02), sex (OR 0.58), fibromyalgia (OR 1.46), obesity (OR 1.24), tobacco use (OR 1.60), and preoperative opioid use (OR, 1.86). Recurrent instability was found in 1,012 (8.3%) patients, and tobacco use (OR, 1.60) and preoperative opioid use (OR, 1.29) were significantly predictive (P < .01). Conclusions: Factors predictive of return to ED 1 year after arthroscopic shoulder stabilization included female sex, fibromyalgia diagnosis, obesity, tobacco use, preoperative opioid use, and postoperative recurrent instability. Factors predictive of opioid use 1 year postoperatively included female sex, obesity, tobacco use, and recurrent instability but not preoperative opioid use. Factors predictive of recurrent instability included female sex and tobacco use. Level of Evidence: Level IV, prognostic study.